2010
DOI: 10.1016/j.margen.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a second SALMFamide gene in the sea urchin Strongylocentrotus purpuratus reveals that L-type and F-type SALMFamide neuropeptides coexist in an echinoderm species

Abstract: The SALMFamides are a family of neuropeptides that act as muscle relaxants in the phylum Echinodermata. Two types of SALMFamides have been identified in echinoderms: firstly, the prototypical L-type SALMFamide peptides with the Cterminal sequence Leu-X-Phe-NH 2 (where X is variable), which have been identified in several starfish species and in the sea cucumber Holothuria glaberrima; secondly, F-type SALMFamide peptides with the C-terminal sequence Phe-X-Phe-NH 2 , which have been identified in the sea cucumbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…These findings demonstrated that known neuropeptide precursors are represented amongst the collection of 2026 radial nerve ESTs analysed, providing an important indication that more detailed scrutiny of the EST dataset might reveal additional neuropeptide precursors. The first novel neuropeptide precursor identified by analysis of the EST dataset was the L-type SALMFamide precursor reported previously [68], which we have designated as ''S. purpuratus neuropeptide precursor 1'' or Spnp1 (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings demonstrated that known neuropeptide precursors are represented amongst the collection of 2026 radial nerve ESTs analysed, providing an important indication that more detailed scrutiny of the EST dataset might reveal additional neuropeptide precursors. The first novel neuropeptide precursor identified by analysis of the EST dataset was the L-type SALMFamide precursor reported previously [68], which we have designated as ''S. purpuratus neuropeptide precursor 1'' or Spnp1 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Here we present a complementary strategy, namely the analysis of expressed sequence tag (EST) data obtained from a S. purpuratus nerve cord cDNA library. We recently demonstrated the utility of this approach with the identification of a second SALMFamide precursor gene in S. purpuratus (Spnp1; [68]) and here we have extended the use of this approach with the identification of 19 other putative neuropeptide precursor genes (Spnp2 -Spnp20). The data presented here provide novel insights on the evolution of neuropeptide signaling systems as well as providing a basis for studies in which the expression and physiological/ behavioral roles of neuropeptides are investigated in a model echinoderm species.…”
Section: Introductionmentioning
confidence: 89%
“…Three of these are also putative F-type SALMFamide neuropeptides: ARYSPFTFamide, GHRGGQFSQFKFamide and FKSSFYLamide. However, the third peptide, FKSSFYLamide, is unusual because it has a C-terminal leucine residue, whereas all of the SALMFamide neuropeptides previously identified in echinoderms have a C-terminal phenylalanine residue [14], [29]. In addition, the precursor contains the putative peptide GVPPYVVKVTYamide, which exhibits even greater structural divergence from the SxL/FxFamide motif that characterises SALMFamides.…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting because analysis of sequence data from the sea urchin S. purpuratus revealed that in this species F-type and L-type SALMFamide neuropeptides are encoded by different genes, with seven F-type SALMFamides (SpurS1 – SpurS7) derived from one precursor protein and two L-type SALMFamides (SpurS8 and SpurS9) derived from a second precursor protein [29], [30]. The existence of a SALMFamide precursor in A. japonicus containing both F-type and L-type SALMFamides may reflect conservation of a characteristic of the common ancestor of sea cucumbers and sea urchins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation